2022
DOI: 10.1039/d1em00511a
|View full text |Cite
|
Sign up to set email alerts
|

A novel Ca/Mn-modified biochar recycles P from solution: mechanisms and phosphate efficiency

Abstract: The excessive use of phosphate leads to severe environmental issues, such as shortage of phosphorus resources and water eutrophication. In this study, a novel Ca-Mn-impregnated biochar (CMBC) composite was synthesized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Studies focused on Cd (II) sorption via phosphate-loaded Ca-Mn-impregnated biochar (P s -CMBC; prepared via the phosphate sorption process on CMBC) are limited. Our previous studies prepared Ca-Mn-impregnated biochar by modifying biochar with CaCl 2 and KMnO 4 , which increased the adsorption active sites and microporous structure of CMBC and showed that CMBC had excellent sorption performance in phosphate removal from solution, and that CMBC possesses stable properties and strong buffering capacity [25]. Thus, we hypothesized that P s -CMBC may have more capacity for adsorption of Cd due to the presence of P in the biochar.…”
Section: Introductionmentioning
confidence: 98%
“…Studies focused on Cd (II) sorption via phosphate-loaded Ca-Mn-impregnated biochar (P s -CMBC; prepared via the phosphate sorption process on CMBC) are limited. Our previous studies prepared Ca-Mn-impregnated biochar by modifying biochar with CaCl 2 and KMnO 4 , which increased the adsorption active sites and microporous structure of CMBC and showed that CMBC had excellent sorption performance in phosphate removal from solution, and that CMBC possesses stable properties and strong buffering capacity [25]. Thus, we hypothesized that P s -CMBC may have more capacity for adsorption of Cd due to the presence of P in the biochar.…”
Section: Introductionmentioning
confidence: 98%
“…The growing world population and crop demand increased the phosphorus fertilizer consumption (Xu et al 2018). The global use of phosphorus fertilizer has resulted in the migration of millions of tons of P 2 O 5 from soil into aquatic environment, which increased the phosphate levels in water (Wang et al 2022). Existing studies demonstrated that the content of phosphate in water exceeding 0.02 mg/L would result in eutrophication (Wang et al 2019), triggering the rapid propagation of algae, deterioration of water quality, and ecological equilibrium (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the adsorption property of phosphates, the biochar must be modified. Calcium (Ca), which is an environmentally friendly, cheap, and widely abundant metal, could effectively remove phosphate (P) from solution [11][12][13]. Ca loaded on other carrier materials, such as biochar, can be effective adsorbents for the recovery of phosphorus from wastewater [14].…”
Section: Introductionmentioning
confidence: 99%